Atención al cliente en la Ferretería Don Víctor en la ciudad de Babahoyo, periodo 2023. - Minga Montece, Brando Alexander (2024)
Customer service in a hardware store is crucial for ensuring customer satisfaction and the long-term success of the business. The case study examined the significance of customer expectations and how they can significantly impact poor customer engagement and business outcomes if improvements are not made in customer service and marketing campaign implementation, as well as adaptation to modern consumer needs with digital tools. Our analysis demonstrates that exceptional customer service not only fosters customer retention but can also enhance customer loyalty and result in positive reviews, consequently attracting new customers. To achieve outstanding customer service, it is imperative that hardware store employees are well-prepared, friendly, attentive, and readily available to assist customers at all times. Employee Training: Providing employees with appropriate training in customer service, including communication skills, problem-solving abilities, and product knowledge, is essential. A well-prepared staff member can offer expert advice and guidance to customers, significantly enhancing business efforts by maximizing employee competency in resolving customer issues promptly and effectively.